2016
DOI: 10.3109/10520295.2015.1136988
|View full text |Cite
|
Sign up to set email alerts
|

Irisin immunohistochemistry in gastrointestinal system cancers

Abstract: Cancer is the leading cause of morbidity and mortality worldwide. Some studies have shown that high heat kills cancer cells. Irisin is a protein involved in heat production by converting white into brown adipose tissue, but there is no information about how its expression changes in cancerous tissues. We used irisin antibody immunohistochemistry to investigate changes in irisin expression in gastrointestinal cancers compared to normal tissues. Irisin was found in human brain neuroglial cells, esophageal epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 35 publications
3
64
2
Order By: Relevance
“…All these findings together with our present results suggest that irisin might be a new diagnostic indicator of the presence of cancer. However, in disagreement with these results, studies performed by Aydin et al (2016) revealed a significant increased irisin immunoreactivity in colon adenocarcinoma tissue compared with that in normal colon tissues in Turkish people. In vitro studies performed by Moon and Mantzoros (2014) showed that irisin at both physiological and pharmacological concentrations has no effects on cell proliferation, cell adhesion, and/or colony formation in HT29 and MCA38 colon cancer cell lines.…”
Section: Discussionmentioning
confidence: 79%
“…All these findings together with our present results suggest that irisin might be a new diagnostic indicator of the presence of cancer. However, in disagreement with these results, studies performed by Aydin et al (2016) revealed a significant increased irisin immunoreactivity in colon adenocarcinoma tissue compared with that in normal colon tissues in Turkish people. In vitro studies performed by Moon and Mantzoros (2014) showed that irisin at both physiological and pharmacological concentrations has no effects on cell proliferation, cell adhesion, and/or colony formation in HT29 and MCA38 colon cancer cell lines.…”
Section: Discussionmentioning
confidence: 79%
“…However, the sample size in that study was too small and they did not compare FNDC5/irisin expression between HCC tissues and adjacent noncancer tissues. Using irisin immunohistochemistry, Aydin et al has showed that irisin expression was significantly increased in various gastrointestinal cancers, but not in HCC [6]. Irisin inhibits gluconeogenesis [13] and the liver plays key roles in the regulation of glucose production [14].…”
Section: Discussionmentioning
confidence: 99%
“…In cultured breast cancer cells, irisin reduced cell proliferation, viability, and migration and enhanced the cytotoxic effect of doxorubicin [4]. However, in HCC, one study showed that irisin expression was upregulated in HCC tissues [5], while another study did not [6]. These contradictory results indicate the complexity of the irisin expression/regulation in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…It is synthesized in many tissues including skeletal muscle and fat cells, and participates in the regulation of lipid and glucose metabolism (Aydin, 2014). Since irisin regulates fat metabolism, it plays an important role in the emergence and development of obesity, insulin resistance associated with obesity, diabetes, non-alcoholic fatty liver disease and other metabolic diseases (Aydin et al, 2016;Zhu et al, 2018). By increasing levels of uncoupling protein-1 (UCP1), Irisin converts white adipose tissue cells into brown adipose tissue cells and reduces obesity (Boström et al, 2012).…”
Section: Introductionmentioning
confidence: 99%